The importance of arbuscular mycorrhiza for Cyclamen purpurascens subsp. immaculatum endemic in Slovakia - Rydlová, Jana; Sýkorová, Zuzana; Slavíková, Renata; Turis, Peter (Mycorrhiza, 2015)
At present, there is no relevant information on arbuscular mycorrhiza and the effect of the symbiosis on the growth of wild populations of cyclamens. To fill this gap, two populations of Cyclamen purpurascens subsp. immaculatum, endemic in Nízke Tatry (NT) mountains and Veľká Fatra (VF) mountains, Slovakia, were studied in situ as well as in a greenhouse pot experiment. For both populations, mycorrhizal root colonization of native plants was assessed, and mycorrhizal inoculation potential (MIP) of the soils at the two sites was determined in 3 consecutive years. In the greenhouse experiment, the growth response of cyclamens to cross-inoculation with arbuscular mycorrhizal fungi (AMF) was tested: plants from both sites were grown in their native soils and inoculated with a Septoglomus constrictum isolate originating either from the same or from the other plant locality. Although the MIP of soil at the NT site was significantly higher than at the VF site, the level of AMF root colonization of C. purpurascens subsp. immaculatum plants in the field did not significantly differ between the two localities. In the greenhouse experiment, inoculation with AMF generally accelerated cyclamen growth and significantly increased all growth parameters (shoot dry weight, leaf number and area, number of flowers, tuber, and root dry weight) and P uptake. The two populations of C. purpurascens subsp. immaculatum grown in their native soils, however, differed in their response to inoculation. The mycorrhizal growth response of NT plants was one-order higher compared to VF plants, and all their measured growth parameters were stimulated regardless of the fungal isolates' origin. In the VF plants, only the non-native (NT originating) isolate showed a significant positive effect on several growth traits. It can be concluded that mycorrhiza significantly increased fitness of C. purpurascens subsp. immaculatum, despite the differences between plant populations, implying that AMF symbionts should be taken into account in conservation programs of this endemic plant.
Keywords: půdní mikrobiologie; Cyclamen; mykorhiza; Phylogeny; Mycorrhizae; Slovakia; Slovenská republika; symbióza; fylogeneze; Plant Roots; kořeny rostlin; Symbiosis; Soil Microbiology